The Effect of Crime on Foreign Investment and Economic Development in Sub-Saharan Africa: A Panel Data Analysis (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the effect of crime on economic development in 22 sub-Saharan African countries between 2000 and 2020, using data from global sources. The study utilized a panel vector autoregression (VAR) approach to analyze the dynamic correlations between variables. This was achieved through the examination of impulse response functions and error variance decomposition. The study established a definitive cause-and-effect connection between the crime rate and growth indicators. The panel vector autoregression (VAR) technique resolves the issue of endogeneity by permitting endogenous interaction among the variables in the system. The findings indicate that the crime rate has a significant effect on economic growth in sub-Saharan countries, though with very low magnitude. The economic prosperity of most sub-Saharan African countries may be attributed to the abundant availability of natural resources in the region. The causality test findings indicate a diverse causal connection between the crime rate and growth indicators. While there is no direct causal relationship between economic growth and the crime rate, there is a one-way causality between economic growth and foreign investment. This means that economic growth can enhance foreign investment, suggesting that in sub-Saharan countries, economic growth plays a crucial role in improving foreign investment. However, as indicated by the findings, there exists a bidirectional causal relationship between foreign investment and crime rates. In summary, it is clear that the crime rate in sub-Saharan African nations has a significant impact. In the future, countries with higher crime rates are likely to see slow economic growth and less foreign investment.